(untitled) (Biological Sciences - PJSIR, 1997)
The genus Potamogeton belongs to the family Potamogetonaceae and comprises five species with interest- ing but diverse uses in folklore medicine. For instance Potamogeton pectinatus L. is used to relieve fever of the liver, while P. javanicus Hassk and P. natans L. are febrifuge and resolvent [1]. A decoction of P. polygonifelius Pourr., with brown sugar, is ingested to treat dysentery; a simple decoc- tion affords a treatment for toothache and eye diseases [1]. The medicinal properties of this genus have prompted us to carry out phytochemical studies on one of its species P. pectinatus which commonly occurs in various parts of East and Southeast Asia. The literature survey reveals that no individual constituent has ever been isolated from this. species although some amino acids and carbohydrates have been identified through chromatography [2-31. Herein we report the isolation and characterization of a new purine al- kaloid and an aromatic diester from P. pectinatus collected form Oven Lake in Almoot District, Tehran.